THE PAULIAN ACTION WITHIN THE REGULATORY CONTEXT OF LAW 287/2009 CONCERNING THE CIVIL CODE - Bularca Anca Roxana (Bulletin of Transilvania University of Brasov, 2014)
The term Paulian Action originates in Roman law, where it was a class action carried in the name of all creditors by a curator bonorum, with the effect of obligating the debtor to pay the defrauded creditors an amount equal to the value of the alienated assets. As will be shown, in current legal practice the action is individual and benefits only the creditor who files suit. The term of revocatory action was coined by its main effect, namely of inter partes rescinding of the attacked deeds, which in modern law is considered synonymous to non-opposability.